Traffic Engineering with Rerouting in Diffserv MPLS Networks - Phang, K.K.; Ling, T.C.; Ang, T.F. (Malaysian Journal of Computer Science, 2012)
An important aspect of traffic engineering is the re-optimization of network resources. In this process, traffic over a congested path is rerouted to a new path to improve efficiency in network resource utilization. The aggregation nature of DiffServ MPLS networks often gives rise to long-lived flows within the network. A rerouting mechanism that supports the tearing-down of old connections and the setting-up of new connections is essential. In the absence of a rerouting mechanism, long-lived flows will be tied to inefficient paths for an extended period of time. A simple non-shortest path rerouting algorithm, namely SimpleReroute (SRR), is proposed. The simulation results indicate that SRR exhibits a lower packet loss ratio. SRR is able to reduce packet loss up to about 15 orders of magnitude, i.e. reducing the packet loss percentage from as high as 14.9% to 1% when the network is heavily congested.